The role of clinical supervision in transforming novice physical therapists into compassionate clinicians - Anwar, Sahreen; Perveen, Wajida (Deka in Medicine, 2025)
Clinical supervision is a pivotal process in developing beginning physical therapy practitioners into proficient clinicians. Transcending from internee to clinician requires systematic mentoring in order to gain confidence, professional identity, and therapeutic competencies. Physical therapy differs from other medical specialties with standardized diagnostic machines; rather, it is based on the clinical competence of the assessor in diagnosing and treating patients. Successful supervision enhances clinical proficiency alongside empathy, communication, and integrative patient care. However, maximizing supervision of physical therapy education continues to be a challenge. Clinical mentorship helps novice therapists present complex medical concepts in brief and empathetic terms to enhance trainees' as well as instructors' benefits. Successful rehabilitation communication has been linked to enhanced patient outcomes through research. Supervision also facilitates clinical decision-making by integrating evidence-based practice with interdisciplinary practice. Nevertheless, increased reliance on technology and artificial intelligence calls for technology-balancing with real-time mentorship. One of the primary supervision issues is the knowledge gap between supervisors and trainees. The majority of experienced clinicians have not been formally trained in educational techniques, which can undermine the quality of mentorship. Additionally, the rising prevalence of musculoskeletal disorders due to overuse of electronic devices necessitates new clinical knowledge, which needs to be integrated into training. Clinical supervision is crucial for the production of competent physical therapists. Mentorship can also be made more effective by supplementing it with formal training programs for supervisors and incorporating emerging healthcare issues into training. Strengthened clinical supervision will lead to better professional development, evidence-based decision-making, and finally better-quality patient care.